2012
DOI: 10.3182/20120710-4-sg-2026.00059
|View full text |Cite
|
Sign up to set email alerts
|

Process performance analysis in large-scale systems integrating different sources of information

Abstract: Process auditing using historical data can identify causes for poor performance and reveal opportunities to improve process operation. To date, the data used has been limited to process measurements; however other sources hold complementary information about the process behavior. This paper proposes a new approach to root-cause diagnosis, which also takes advantage of the information in utility, mechanical and electrical data, alarms and diagrams. Its benefit is demonstrated in an industrial case study, by tac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Representation of information from engineering systems has traditionally been a technology focused area. Recent research in the field of process operations, (Cecilio et al, 2012), and (Yang and Xiao, 2012), showed that users need better support from engineering tools in order to cope with the complexity imposed by modern installations. I will hereby refer to software applications as 'tools'.…”
Section: Visualization Of Connectivitymentioning
confidence: 99%
“…Representation of information from engineering systems has traditionally been a technology focused area. Recent research in the field of process operations, (Cecilio et al, 2012), and (Yang and Xiao, 2012), showed that users need better support from engineering tools in order to cope with the complexity imposed by modern installations. I will hereby refer to software applications as 'tools'.…”
Section: Visualization Of Connectivitymentioning
confidence: 99%
“…Previous investigations in this topic [4,5] have pointed out that there is a need for tools that can integrate various quantitative and qualitative methods in fault propagation analysis. Yet, to date, there has been little work on creating tools that are able to efficiently integrate and represent plant topology information.…”
Section: Introductionmentioning
confidence: 99%